ORGANIZATIONAL COMMUNICATION PLAN PT. MITRA PRESTASI PERDANA TO ACHIEVE EMPLOYEE PRODUCTIVITY FOR THE 2020-2021 PERIOD - Yudinta, Dewa Putu Dharma; Syaifuddin, Syaifuddin (IJOSMAS, 2023)
In the initial stages of the Covid-19 pandemic's entry into Indonesia in March 2020, the Indonesian government introduced a mandate for companies to adopt a Work From Home (WFH) arrangement. The objective of this directive was to curtail in-person interactions among individuals, which had the potential to propagate the Covid-19 virus. Consequently, all enterprises, including PT. Mitra Prestasi Perdana, enforced a comprehensive Work From Home policy for their entire workforce.Over the course of the three-month period in which the Work From Home policy was in effect, there were instances of decreased work productivity among some employees. This decline in productivity stemmed from multiple factors such as inadequate communication among colleagues and a sense of monotony at work due to the absence of face-to-face engagement with co-workers in the context of full remote work. In response, PT. Mitra Prestasi Perdana devised a modified approach consisting of three days of remote work and two days of in-office work per week. Additionally, they implemented an orchestrated communication strategy with the goal of revitalizing employee work productivity. This research is characterized as a qualitative descriptive study employing the case study research methodology. The investigation delved into how communication planning was executed at PT. Mitra Prestasi Perdana, using Charles Berger's planning theory as a framework. The findings of this study underscore that PT. Mitra Prestasi Perdana's organizational communication strategy effectively revitalized employee work productivity, which had experienced a decline during the three-month period of exclusive remote work. The company's weekly meetings orchestrated by management fostered direct interactions between leaders and employees, thereby facilitating effective communication. Furthermore, the leaders' approach of cultivating a friendly rapport with employees, coupled with provisions such as meals and recreational amenities, contributed to fostering a comfortable work environment.